Land use and population growth of Primula veris: an experimental demographic approach - Ehrlen, J; Syrjanen, K; Leimu, R; Garcia, M; Lehtila, K (2005)
1. Changes in land use are the primary cause of decline for many plant species. Efficient management actions for such species must be based on knowledge of the key phases of the plant life cycles that respond most to changes in environmental factors. 2. To assess how grazing influences population viability of the perennial rosette herb Primula veris, we applied four experimental treatments to abandoned grasslands and recorded the demographic response in permanent plots and seed sowing experiments over 3 years. 3. Treatments had strong effects on population viability. Transition matrix models showed that cutting the surrounding vegetation had no effect on population growth rate (λ). However, when this was combined with litter removal λ increased to 1.46, compared with 1.11 in controls. With disturbance and complete removal of the surrounding vegetation the effect was even stronger, and λ increased to 1-60. 4. Increases in λ were primarily a result of increased growth of the smallest rosettes, and increased seedling production. In contrast, the performance of larger P. veris individuals was not affected by experimental treatments. 5. The higher the elasticity of a particular life cycle transition, the less the change in the transition rate caused by treatments. This suggests that plants are able partly to buffer the effects of environmental variation by minimizing changes in the life cycle transitions that are most important to population growth rate. 6. Synthesis and applications. Experimental demographic approaches provide an important tool for assessing how grazing and other types of management influence species viability, and help to unravel the mechanisms underlying such relationships. With such information it is possible to predict the effects of novel types of management and land-use scenarios on population viability. For P. veris, we identified seedling establishment as a key phase in the life cycle, and litter accumulation as a key environmental factor, suggesting that these should be prime targets for management. One practice that is likely to favour as well as seedling establishment preventing litter accumulation is late summer grazing. © 2005 British Ecological Society.